Introducing Partial Transformation UP-Algebras (European Journal of Pure and Applied Mathematics, 2018)
The main aim of this paper is to introduce the notion of a partial transformation UP-algebra $P(X)$ induced by a UP-algebra $X$ and prove that the set of all full transformations $T(X)$ is a UP-ideal of $P(X)$.
Keywords: UP-algebra; partial transformation; full transformation.